1960
DOI: 10.1080/00288233.1960.10419871
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing survival of strains of ryegrass during the summer

Abstract: SummaryThe influence of levels of temperature, soil moisture, soil nitrogen status, and of light intensity on the survival of New Zealand strains of ryegrass (Lolium spp.) was examined.It was found that not only was the survival of plants reduced bv soil moisture stress (pF 3.4-4.2 compared with pF 2.6-3.0) and high temperature (80°F compared with 65°F), but also that survival under the low moisture or high temperature condition was much less when there was a high level of nitrogen in the soil. The various eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1960
1960
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…It is considered that the main cause of non-attainment of potential yield in the present experiment was summer drought (periods 3 and 7), particularly in the second year. Because of the drought susceptibility of Manawa (Lucanus, Mitchell, Pritchard, and Calder 1960), this cultivar was affected more in this way than Ruanui. Also, as the technique involved the cutting of all plots at the same times, it was inevitable that the timing of defoliation was not optimum for either cultivar at all times to attain maximum regrowth in respect to efficient light interception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered that the main cause of non-attainment of potential yield in the present experiment was summer drought (periods 3 and 7), particularly in the second year. Because of the drought susceptibility of Manawa (Lucanus, Mitchell, Pritchard, and Calder 1960), this cultivar was affected more in this way than Ruanui. Also, as the technique involved the cutting of all plots at the same times, it was inevitable that the timing of defoliation was not optimum for either cultivar at all times to attain maximum regrowth in respect to efficient light interception.…”
Section: Discussionmentioning
confidence: 99%
“…The dominance of Manawa continued into period 3 for all cutting systems, even though the yield of Rl.O was greater than that of Ml.O. Ruanui yielded more than Manawa at this stage because it was more able to withstand drought (Lucanus et al 1960) and had fewer reproductive tillers (Brougham 1961). Observations indicated that during yield period 3 many Manawa plants died, and this opened the way for dominance of Ruanui under the frequent systems of cutting and where cutting was initially infrequent and lax.…”
Section: Discussionmentioning
confidence: 99%
“…High productivity and good persistence of Italian ryegrasses in Southland (Armstrong 1981) contrasts with other environments in New Zealand (Percival et al 1989;. In other regions, Argentine stem weevil damage is greater, summer moisture stress is more severe and occurs more frequently, and summer temperatures are higher, all factors that greatly reduce plant persistence of Italian and hybrid ryegrasses (Lucanus et al 1960;Harris 1970;Hume 1993).…”
Section: Ryegrass Productionmentioning
confidence: 99%
“…This was most probably linked to the infrequently grazed pastures reaching ceiling yield before grazing (Scott 1976) and suffering senescence as a result of excessive herbage accumulation (Brougham 1956;Hickey & Baxter 1989). Italian and hybrid ryegrasses generally require infrequent grazing for high productivity and persistence, particularly during periods of high temperatures and low soil moistures in summer (Mitchell 1954;Lucanus et al 1960;Brougham 1960Brougham ,1961. However, considering the importance placed on producing high-quality summer pastures in Southland, desirable grazing management strategies may include more frequent grazing to maximise pasture quality rather than yield.…”
Section: Grazing Frequencymentioning
confidence: 99%
“…Under dry summer conditions, perennial ryegrass tends to become dormant and there is a delay of 2-3 weeks between the onset of effective autumn rains and the beginning of new tiller formation (Silsbury 1964). Lucanus et al (1960) showed that the survival rate of perennial ryegrass over the summer was reduced by low soil moistures and high temperatures. Survival was further reduced if soil N was at a high level.…”
Section: Methodsmentioning
confidence: 99%